B cell fate mapping reveals their contribution to the memory immune response against helminths - Haase, Paul; Schäfer, Simon; Gerlach, Roman G.; Winkler, Thomas H.; Voehringer, David (Frontiers in Immunology, 2022)
An estimated quarter of the human world population is infected with gastrointestinal helminths causing major socioeconomic problems in endemic countries. A better understanding of humoral immune responses against helminths is urgently needed to develop effective vaccination strategies. Here, we used a fate mapping (FM) approach to mark germinal center (GC) B cells and their developmental fates by induced expression of a fluorescent protein during infection of mice with the helminth Nippostrongylus brasiliensis. We could show that FM+ cells persist weeks after clearance of the primary infection mainly as CD80+CD73+PD-L2+ memory B cells. A secondary infection elicited expansion of helminth-specific memory B cells and plasma cells (PCs). Adoptive transfers and analysis of somatic mutations in immunoglobulin genes further revealed that FM+ B cells rapidly convert to PCs rather than participating again in a GC reaction. These results provide new insights in the population dynamics of the humoral immune response against helminths.